Language Attitudes and Valorization Among Indonesianan Engineering Students - Nurlia, Vera; Indarti, Dwi; Manara, Christine (Universitas Pendidikan Mandalika, 2025)
This study explores the attitudes and valorization of languages among Indonesian engineering students at Cendikia Abditama University. Employing a qualitative research design, the study gathered data from 70 students through questionnaires, supplemented by in-depth interviews with 10 participants to gain richer perspectives. A descriptive analytical approach was used to interpret the findings, revealing a predominantly positive attitude toward English, Indonesian, and heritage languages. This demonstrates a nuanced balance between cultural pride, national identity, and the global opportunities associated with these languages. The research highlights that while many students value all three languages equally, others exhibit a preference for one language over the others, depending on their immediate academic, professional, or personal aspirations. These variations reflect the dynamic interplay between cultural heritage and global competitiveness in shaping language attitudes. The findings underline the critical role of educational policies in supporting linguistic diversity and fostering inclusive learning environments. By integrating students’ linguistic backgrounds into educational curricula, institutions can enhance learning experiences and promote multilingual competence. Such approaches can help prepare students for the challenges of a globalized world while maintaining their cultural roots, thereby contributing to more comprehensive and meaningful educational practices. This study emphasizes the significance of aligning language education with students' diverse needs and aspirations.